2016
DOI: 10.3945/jn.115.229476
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Immunomodulatory Effects of a Mediterranean Diet in Adults at High Risk of Cardiovascular Disease in the PREvención con DIeta MEDiterránea (PREDIMED) Randomized Controlled Trial

Abstract: The MedDiet participants had lower cellular and plasma concentrations of inflammatory markers related to atherosclerosis at 3 and 5 y. This anti-inflammatory role of the MedDiet could explain in part the long-term cardioprotective effect of the MedDiet against CVD. This trial was registered at controlled-trials.com as ISRCTN35739639.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
109
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(120 citation statements)
references
References 41 publications
5
109
0
6
Order By: Relevance
“…Results of different epidemiologic studies have suggested that there may be a connection between frequent nut consumption and decreased incidences of several chronic diseases [24]. Recent emerging scientific studies have demonstrated that the bioactive constituents of nuts have cardioprotective, antiobesity, anticancer, and antioxidant effects mediated by different mechanisms in the human body [25,26]. The results obtained in this study are in accordance to fatty acids levels from Macadamia seeds reported in different studies in the science literature.…”
Section: Discussionsupporting
confidence: 89%
“…Results of different epidemiologic studies have suggested that there may be a connection between frequent nut consumption and decreased incidences of several chronic diseases [24]. Recent emerging scientific studies have demonstrated that the bioactive constituents of nuts have cardioprotective, antiobesity, anticancer, and antioxidant effects mediated by different mechanisms in the human body [25,26]. The results obtained in this study are in accordance to fatty acids levels from Macadamia seeds reported in different studies in the science literature.…”
Section: Discussionsupporting
confidence: 89%
“…Mendelian randomization studies also indicated that low‐grade systemic inflammation can negatively affect resistance to the development of CVD and cancer . Moreover, the Mediterranean diet intervention in the PREvención con DIeta MEDiterránea (PREDIMED) randomized controlled trial resulted in lower levels of inflammatory markers and reduced risk of CVD .…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, several mechanisms have been proposed to explain how the MeDiet exerts its anti-inflammatory properties. Some evidence show that the MeDiet or some of its main foods could modulate the expression of genes related to plaque stability such as MMP-9 [21], or they may diminish the plasma levels of IL-18 [12], sSelectin-1, sICAM-1, and sVCAM-1 or other biomarkers of inflammation (TNFR-60, TNFR-80, IL-6, and CRP) [1215, 17]. Thus, consumption of a tomato-based drink for 26 days lowered TNF- α secretion by 34% [22], while the consumption of EVOO and vegetables was associated with a reduction of circulating TNFR-60 [14].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, GMCSF produces M1-polarized cells with antigen presentation capacities, which express TNF- α and other proinflammatory cytokines such as IL-1 β , IL-6, IL-8, and IL-12 [30]. The results of other studies [1215, 17] agree with these results, and accordingly, both MeDiets showed an improvement in the chemokines (MCP-1, MIP-1 β , RANTES, and ENA78), colony-stimulating (GCSF and GMCSF), cytokines (IL-1 β , 5, 6, 7, 8, 12, TNF- α , and IFN- γ ), and vulnerability plaque marker (IL-10, 13, and 18) levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation